Pengaruh Sikap, Kesadaran Wajib Pajak, dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dalam Membayar PBB - Nabila Maghfira; Yenni Samri Juliati Nst; Nurwani (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
The content of this research aims to determine the influence of attitudes, taxpayer awareness and tax knowledge on taxpayer compliance in paying land and building taxes in Medan Polonia City. This research uses a quantitative method with an associative approach, namely research that emphasizes analysis on numerical data (numbers) processed using statistical methods. The data collection technique used a questionnaire with a sample size of 50 people in Polonia, Medan City. The sampling technique uses saturated samples. Data were analyzed using multiple linear regression methods. The results of this research show that taxpayer attitudes have a significant effect on taxpayer compliance in paying land and building taxes. Taxpayer awareness has a significant effect on taxpayer compliance in paying land and building taxes. Tax knowledge has a significant effect on taxpayer compliance in paying land and building taxes. Taxpayer attitudes, taxpayer awareness and tax knowledge simultaneously have a significant effect on taxpayer compliance in paying land and building taxes.